New method for low temperature fabrication of Ni-Al alloy powder for molten carbonate fuel cell applications - Jang, Seong-Cheol; Lee, Byung Yong; Nam, Suk Woo; Ham, Hyung Chul; Han, Jonghee; Yoon, Sung Pil; Oh, Seong-Geun (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Lump-free Ni-5 wt% Al alloy powder was successfully prepared using an AlCl3 activator at 400 degrees C under vacuum. The AlCl3 activator served as the catalyst, lowering the fabrication temperature by 1000 degrees C compared with the temperature required for the conventional process. The Ni-Al alloy was formed by the following steps: the formation of NiAl by the reaction of the Ni surface with AlCl2 or AlCl produced by the reaction between Al and AlCl3, the formation of Ni3Al by Al diffusion and reaction, and the formation of a Ni-Al solid solution by Al diffusion into the Ni matrix until the solubility limitation was reached. Although lowering the alloying temperature lengthens the reaction time, the time could be reduced by controlling the amount of AlCl3. A single cell test and a creep test were also conducted using a green sheet of as-prepared Ni-Al alloy powder as an anode of a molten carbonate fuel cell (MCFC). Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: PERFORMANCE; OPERATION; ELECTRODE; CATHODES; ANODES